2020
DOI: 10.48550/arxiv.2012.01240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bottomonium suppression in an open quantum system using the quantum trajectories method

Abstract: We solve the Lindblad equation describing the Brownian motion of a Coulombic heavy quark-antiquark pair in a strongly coupled quark-gluon plasma using the highly efficient Monte Carlo wave-function method. The Lindblad equation has been derived in the framework of pNRQCD and fully accounts for the quantum and non-Abelian nature of the system. The hydrodynamics of the plasma is realistically implemented through a 3+1D dissipative hydrodynamics code. We compute the bottomonium nuclear modification factor and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 83 publications
2
16
0
Order By: Relevance
“…Since these early works, it has been shown that it is equally important to include effects of in-medium singlet-octet transitions and Landau damping of the exchanged gluons, which results in an imaginary contribution to the heavy-quark (HQ) potential [5][6][7][8][9][10][11][12][13][14]. These effects can be modelled systematically using numerical solutions of the Lindblad equation which governs the evolution of the in-medium heavy-quarkonium reduced density matrix [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Since these early works, it has been shown that it is equally important to include effects of in-medium singlet-octet transitions and Landau damping of the exchanged gluons, which results in an imaginary contribution to the heavy-quark (HQ) potential [5][6][7][8][9][10][11][12][13][14]. These effects can be modelled systematically using numerical solutions of the Lindblad equation which governs the evolution of the in-medium heavy-quarkonium reduced density matrix [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…There is a formalism, called open quantum systems, in which the quarkonium bound state is considered in interaction with the surrounding thermal medium [36]. This formulation makes use of effective field theories, as appropriate for heavy quarks, and the input in calculation is expressed by a small number of rigorously defined calculable quantities [37][38][39][40]. Figure 15 shows an example of such a calculation, done last year by Xiaojun Yao, a former Duke graduate student now at MIT, who showed that with reasonable values for these parameters one could nicely explain the suppression of the heavy Upsilon (bb) states, the 1S state and the 2S state, in a QGP [37,41].…”
Section: Diagnostics Sensitive To Gluonsmentioning
confidence: 99%
“…The observation of sequential bottomonium suppression [1][2][3][4][5] in relativistic heavy-ion collisions at LHC has sparked a series of dedicated investigations, e.g. [6][7][8][9][10][11][12][13][14]. Such heavyquark flavor degrees of freedom receive currently some interest as valuable probes of hot and dense strong-interaction matter produced in heavy-ion collisions at LHC energies.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the heavy-quark physics addresses such issues as charm (c, c) and bottom (b, b) dynamics related to transport coefficients [14,[16][17][18][19][20][21] in the rapidly evolving and highly anisotropic ambient quark-gluon medium [22,23] as well as QQ states as open quantum systems [24][25][26][27]. The wealth of experimental data from LHC, and also from RHIC, enables a tremendous refinement of our understanding of heavy-quark dynamics.…”
Section: Introductionmentioning
confidence: 99%